The Shared Pathogenesis of Pulmonary Artery Hypertension - Anggoro Budi Hartopo; Lucia Kris Dinarti (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2018)
Pulmonary artery hypertension is defined as an increased in pulmonary artery pressureexceeding 25 mmHg with normal pulmonary wedge pressure. The pathogenesis of pulmonaryartery hypertension involves interaction among vascular, cellular and biomarker componentsin the pulmonary tissue; with eventual result is elevated pulmonary artery pressure. Vascularcomponents are remodeling of intimal, medial and adventitial layers. Cellular components areplayed by apoptosis-resistant endothelial cells, proliferative-prone pulmonary artery smoothmuscle cells, fibroblasts and inflammatory cells. The functional biomarkers are produced andmediated by these cellular changes, mainly endothelin-1, thromboxane, serotonin, nitric oxide,and prostacyclin. The pulmonary vascular remodeling in pulmonary artery hypertension arediverse and may present in various severity based on underlying etiology. Understanding theshared pathogenesis in pulmonary artery hypertension is of paramount importance in order toimprove the disease management and treatment approach.